Propriedades psicométricas da Escala de Atitudes sobre o Amor (LAS) em universitários peruanos - Paula C. Lascurain Wais (2017)
The aim of this article was to analyze the construct validity and reliability of the Love Attitude Scale (LAS, Hendrick & Hendrick, 1986). The sample consisted of 381 undergraduate students (61.7 % of them women) between the ages of 17 and 25 years old. The LAS and the I- PANAS - SF (adapted by Gargurevich, 2010) that evaluates positive and negative affect were applied. The exploratory factor analysis resulted in six factors (Eros, Ludus, Storge, Pragma, Mania and Ágape), that explained 47.87 % of the total variance. The correlations between the score of Eros and Pragma styles and positive affect were positive and significant; while Manía and Ludus styles had positive and significant relationships with negative affect. Reliability by the method of internal consistency of the six factors found was from .62 to .85; while the stability coefficients for test- retest method were .44 to .77. These results allow concluding that the LAS and their scores are valid and reliable to measure attitudes toward love in the college population of Lima.